2011
DOI: 10.1002/ejlt.201100170
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal availability of conjugated linoleic acids after supplementation to dairy cow diets

Abstract: The objective of the present study was to investigate the effects of a lipid-encapsulated CLA preparation on rumen metabolism and the actual post-ruminal bioavailability of the applied CLA isomers. In the rumen, the CLA supplementation modified the molar proportions of VFA. In period CLA-1 the rumen fermentation shifted toward more butyric acid at the expense of acetic acid. The highest CLA supplementation resulted in increased amounts of isobutyric, isovaleric, and valeric acid. The apparent ruminal digestibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…Investigating the duodenal availability of the same lipid-encapsulated CLA supplement, Pappritz et al [42] showed protection rates of 16% and 5% after providing 3 and 8 g/d of t 10, c 12-CLA, respectively, and assumed an impaired rumen protection due to the pelleting process. Because we used the same conditions for preparing of the CLA supplement, it is most likely that unprotected CLA serve as potential substrates for microbial alterations and, consequently, lead to elevated concentrations of t -18:1 acids.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the duodenal availability of the same lipid-encapsulated CLA supplement, Pappritz et al [42] showed protection rates of 16% and 5% after providing 3 and 8 g/d of t 10, c 12-CLA, respectively, and assumed an impaired rumen protection due to the pelleting process. Because we used the same conditions for preparing of the CLA supplement, it is most likely that unprotected CLA serve as potential substrates for microbial alterations and, consequently, lead to elevated concentrations of t -18:1 acids.…”
Section: Discussionmentioning
confidence: 99%
“…Pappritz et al. () investigated the duodenal availability of a lipid‐encapsulated CLA preparation, which was also used in the present trial. The authors observed, based on intakes of 8 g/day trans ‐10, cis ‐12 CLA, that only 5% of CLA were available in the duodenum, indicating an unexpectedly low rumen protection.…”
Section: Discussionmentioning
confidence: 99%
“…Conjugated linoleic acids have been associated with a modified rumen fermentation pattern as indicated by an altered profile of short‐chain fatty acids. In addition, dietary supplemented CLA increased starch degradation and reduced rumen microbial protein synthesis (Pappritz et al., ). Consequently, CLA may influence rumen parameters like rumen pH (RpH) and rumen temperature (RT).…”
Section: Introductionmentioning
confidence: 99%
“…Daily duodenal dry matter flow (DMF) was calculated according to Pappritz et al. ():DMFkgd=application of0.277778emCr2O30.277778emin mgcowfalse/normald0.277778emCr2O30.277778emin duodenal chyme)(mgg0.277778emDM/1000…”
Section: Methodsmentioning
confidence: 99%
“…Formulas of Schafft (), GfE () and Pappritz et al. () were used to calculate the flow of rumen‐undegraded feed protein (RUP), rumen‐degradable crude protein (RDP), microbial organic matter (mOM), ruminal nitrogen balance (RNB) and ruminal fermented organic matter (FOM):RUPgd=6.25NANgdmicrobial NgdEPgdRDPgd=CP intakegdRUPgdmOMkgd=11.8microbial NkgdRNBgd=)(CP intake0.277778em)(normalgnormalduCP0.277778em)(normalgnormald6.25FOMkgd=OM intakekgdduodenal O...…”
Section: Methodsmentioning
confidence: 99%